2017
DOI: 10.1016/j.athoracsur.2016.12.030
|View full text |Cite
|
Sign up to set email alerts
|

The Carotid Artery as a Preferred Alternative Access Route for Transcatheter Aortic Valve Replacement

Abstract: In our US community hospital setting, TC-TAVR is a safe alternative to TF-TAVR in appropriate patients and has evolved to be our alternative access route of choice if TF access is not feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 14 publications
2
72
0
1
Order By: Relevance
“…Two studies reported shorter fluoroscopy time in favor of TC-TAVR compared with TF-TAVR. 10,11 The decreased use of fluoroscopy in the TC procedure compared with the TSC procedure is likely related to the shorter and straighter distance between the vascular access site and the aortic annulus, requiring less visualization of the valve under fluoroscopy during valve positioning. The decrease in fluoroscopy use may improve overall patient and physician safety, although that should be studied separately.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies reported shorter fluoroscopy time in favor of TC-TAVR compared with TF-TAVR. 10,11 The decreased use of fluoroscopy in the TC procedure compared with the TSC procedure is likely related to the shorter and straighter distance between the vascular access site and the aortic annulus, requiring less visualization of the valve under fluoroscopy during valve positioning. The decrease in fluoroscopy use may improve overall patient and physician safety, although that should be studied separately.…”
Section: Commentmentioning
confidence: 99%
“…The shorter duration of the TC approach was gained without compromising the safety or efficacy of the procedure. Prior studies have shown that the direct aortic and transapical approaches are associated with less favorable outcomes when compared with the TSC and TC approaches, 9,11,18,19 suggesting that either the carotid or the subclavian arteries will become the preferred alternative access sites for TAVR patients.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcatheter aortic valve replacement (TAVR) is rarely performed for aortic regurgitation (AR) in both native and prosthetic valves using transfemoral and transapical access sites . The trans‐carotid approach has been used in patients with patent left internal mammary artery grafts, impaired ventricular function, and severe peripheral vascular disease . However, the trans‐carotid delivery system exchange for a bailout valve‐in‐valve procedure has the potential for severe vascular and neurological complications.…”
Section: Introductionmentioning
confidence: 99%
“…small femoral arteries, extensive obstructive atherosclerotic disease, moderate-severe calcification, and/or severe tortuosity), alternative access sites for TAVR have included trans-apical, trans-subclavian, direct aortic, trans-carotid, and trans-caval. [8][9][10] The vast majority of these alternative access procedures are usually conducted under general anesthesia and carry higher rates of morbidity and mortality; though a selection bias in this patient population certainly exists. 8 Overall, in cases where some or even all "high risk" features are present, there is little in the literature or guidelines to help implanting physicians objectively select one particular access route over the other.…”
mentioning
confidence: 99%